2014
DOI: 10.1093/cid/ciu069
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Multidrug-Resistant Gram-Negative Infections in Children

Abstract: Antibiotic resistance in conjunction with the erosion of the drug development pipeline may lead us into a bleak future, a "post-antibiotic era." Because of a shortage of studies addressing treatment options for multidrug-resistant Gram-negative (MDRGN) infections in children, data must be extrapolated from the adult literature. However, even adult studies are limited by significant methodological flaws. We are in urgent need of pediatric specific pharmacokinetic/pharmacodynamic data for agents with activity ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
122
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(133 citation statements)
references
References 96 publications
3
122
0
8
Order By: Relevance
“…73 A few publications propose potential algorithms for treatment of CRE infection based on molecular detection of specific carbapenemases 74 and carbapenem MIC. 75,76 Infection control implications of rapid detection of CP-CRE Timely identification of individuals who are infected or colonized with CP-CRE would enable prompt implementation of infection control interventions, including patient cohorting and isolation, precautions during invasive procedures and patient transport, and appropriate environmental disinfection. This, in turn, is likely to reduce transmission of CP-CRE within healthcare settings.…”
Section: Treatment Implications Of Rapid Detection Of Crementioning
confidence: 99%
“…73 A few publications propose potential algorithms for treatment of CRE infection based on molecular detection of specific carbapenemases 74 and carbapenem MIC. 75,76 Infection control implications of rapid detection of CP-CRE Timely identification of individuals who are infected or colonized with CP-CRE would enable prompt implementation of infection control interventions, including patient cohorting and isolation, precautions during invasive procedures and patient transport, and appropriate environmental disinfection. This, in turn, is likely to reduce transmission of CP-CRE within healthcare settings.…”
Section: Treatment Implications Of Rapid Detection Of Crementioning
confidence: 99%
“…However, identification of organisms producing ESBLs still has important clinical implications. A portion of these organisms retain in vitro susceptibility to piperacillin-tazobactam and cefepime (2), even though these agents are generally considered inferior to carbapenem therapy for the treatment of invasive infections by ESBL-producing organisms (3)(4)(5).…”
mentioning
confidence: 99%
“…Using the current CLSI ceftriaxone breakpoint of 1 g/ml, we previously found that 100% of 96 organisms expressing AmpC ␤-lactamases had ceftriaxone MICs of Ͼ1 g/ml (11). Ceftriaxone has been found to be problematic for the treatment of these organisms, but broader-spectrum ␤-lactams have not demonstrated such problems (5). Therefore, the coexistence of AmpC ␤-lactamases should be unlikely to impact the ceftriaxone MIC used to trigger ESBL testing.…”
mentioning
confidence: 99%
“…Dosing of colistin in pediatrics is mainly guided by the manufacturer recommendations of a dose of 2.5 mg/kg/dose of colistin base activity (CBA) intravenously every 12 hours. 52 There are no formal studies assessing the use of a loading dose, but several investigators 53 have suggested the use of a loading dose (5 mg/kg of CBA) in order to achieve target serum drug concentration more rapidly. The use of tigecycline in pediatrics is limited by toxicity concerns, and dosing recommendations are based on pharmacokinetic studies (8-11 years: 1.2 mg/kg/dose every 12 hours with a maximum of 50 mg per dose; 12-17 years: 50 mg every 12 hours).…”
Section: Considerations For Pediatricsmentioning
confidence: 99%
“…The use of tigecycline in pediatrics is limited by toxicity concerns, and dosing recommendations are based on pharmacokinetic studies (8-11 years: 1.2 mg/kg/dose every 12 hours with a maximum of 50 mg per dose; 12-17 years: 50 mg every 12 hours). 53 At this time, there are no clinical data or dosing guidance for ceftazidime-avibactam in pediatric patients, although there is an ongoing Phase I study 54 of ceftazidime-avibactam in pediatrics assessing the pharmacokinetics, safety, and tolerability of a single dose in children from 3 months to 18 years of age.…”
Section: Considerations For Pediatricsmentioning
confidence: 99%